From waste to circular economy: Exploring the sustainable potential and engineering properties of self-compacting mortars - Ulucan, Muhammed; Ulas, Merve Acikgenc (Elsevier, 2024)
This study focuses on evaluates 22 produced sustainable self-compacting mortars from a circular economy perspective and explores their engineering properties (durability, economical, environmental, fresh, mechanical, microstructural, and thermal). Pumice and recycled concrete aggregate (RCA) were used as aggregates, silica fume and fly ash as supplementary cementitious materials (SCM). The 90-day compressive strengths indicate that significant strength reductions did not occur until using 10% RCA, while the use of SCM made positive contributions. A comparison of Ref-3 with the 10SF-RCA10 series reveals that the 90-day compressive strength is 39.5-47.9 MPa, respectively, an increase of approximately 21.3%. The results of hightemperature tests revealed significant strength losses, especially in specimens exposed to 600 and 900 degrees C. At 900 degrees C in particular, the compressive strength decreased by 50-70% and the flexural strength by 70-85%. The findings of the thermal conductivity tests emphasize the potential contribution of RCA to the construction of sustainable building materials in evaluating the influence of SSCM on thermal conductivity and energy efficiency. From a microstructural point of view, the use of silica fume and fly ash in certain proportions positively affects the mortar's internal structure, strength and density. For the extensive review of environmental and economic outcomes, global warming and sustainability potential were analyzed using different scenarios. The combined use of RCA and SCM significantly contributes to global warming and sustainability potential. The broad assessment of the economic characteristics revealed that transport distances are crucial and need to be considered for sustainable production.
Keywords: Recycled concrete aggregate; Supplementary cementitious materials; Sustainability potential; Circular economy